Cost Analysis of Road Performance Improvement on Yos Sudarso Road, Baubau City - Jamiludin Nasir; Budi Witjaksana; Jaka Purnama (International Journal Labs, 2026)
Yos Sudarso Road in Baubau City is a major urban corridor that has experienced a decline in traffic performance due to intensive activities in commercial, tourism, and port areas, resulting in high side friction caused by on-street parking and vehicle maneuvering. These conditions reduce the effective road capacity and degrade the level of service. This study aims to estimate the cost required to improve road performance as a basis for practical and applicable traffic management recommendations. The research employs a quantitative approach by identifying improvement alternatives, calculating work volumes, and estimating costs based on the 2022 Indonesian Public Works Unit Price Analysis (Analisa Harga Satuan Pekerjaan, AHSP) for Road and Bridge Works and the 2024 Baubau City Standard Unit Cost (Harga Satuan Pokok Kegiatan, HSPK). The results indicate that traffic management measures in the form of one-side on-street parking arrangement and installation of no-parking traffic signs require a total cost of IDR 57,000,000.00. This cost is relatively economical and effective in improving road capacity and traffic performance without physical road widening.